Stereoanalysis of the Antiparasitic Natural Product Callunene and Its Synthetic Intermediates - Ferenczei, Jiří; Blahout, Vilém; Dvořáková, Hana; Brancale, Andrea; Cuřínová, Petra; Labíková, Magdaléna; Kohout, Michal; Setnička, Vladimír; Perlíková, Pavla (Journal of natural products, 2025)
The recent popularity of indoor farming has brought about problems with parasites spreading among pollinator colonies. The natural product callunene (1) can be used in the prophylaxis of bumblebees against Crithidia infection. Here, we report the synthesis of callunene (1), its enantioseparation, and a method for analyzing its optical purity. The approach was applied to determine the configuration of callunene extracted from heather honey. The proposed method is also applicable to the analysis of mixtures of diastereomers obtained during callunene synthesis, which allows the stereospecificity of individual reaction steps to be determined.
Keywords: Animals; biologické přípravky; Molecular Structure; včely; molekulární struktura; Antiparasitic Agents; Honey; zvířata; antiparazitární látky; med; Biological Products; Stereoisomerism; stereoizomerie; Bees